Evaluation of Well Water Sources in the Residential Area of Sukaregang, Garut, in Relation to Disease Patterns and Contamination by the Leather Processing Industry - Muhammad Nur Abdillah (Sean Institute, 2023)
This study conducts a comprehensive evaluation of well water sources in the Sukaregang residential area, Garut, with a particular focus on the repercussions of disease patterns and contamination attributed to the leather processing industry. The rapid growth of settlements and intensified industrial activities in this region has raised concerns regarding public health and environmental sustainability. The primary objective is to assess well water quality, crucial for the local population, by employing methodologies such as water sampling, laboratory analyses, and community health surveys. The results reveal evidence of well water contamination by waste from the leather processing industry, showcasing a significant correlation with an upsurge in disease patterns within the community. This research pursues dual objectives: first, identifying and analyzing the extent of well water contamination by leather industry waste in Sukaregang, and second, evaluating potential health impacts stemming from the consumption of contaminated well water. The anticipated outcomes seek to establish a robust foundation for the formulation of sustainable environmental and public health policies tailored to the specific dynamics of the Sukaregang residential area in Garut